Target-centred virtue ethics - Swanton, Christine, 1947- (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2021)
"Christine Swanton is Senior Lecturer at the University of Auckland. Her publications include Perspectives in Role Ethics: Virtues, Reasons, and Obligation (co-edited with Tim Dare; Routledge, 2019), The Virtue Ethics of Hume and Nietzsche (Wiley Blackwell, 2015), and Virtue Ethics: A Pluralistic View (Oxford University Press, 2005)"--
Minimal Level Cataloging Plus.
Includes bibliographical references (pages 319-336) and index.
Keywords: Virtue Ethics. -- Philosophy